PEMBERDAYAAN KELOMPOK MASYARAKAT DALAM PENGEMBANGAN AGROEKOWISATA DANAU BONTAK DI NAGARI LUBUK GADANG KABUPATEN SOLOK SELATAN - Rudi Febriamansyah; Sri Setiawati; Elita Amrina; Yuerlita Yuerlita; Fuji Astuti Febria; Jabang Nurdin; Purnawan Purnawan; Yonariza Yonariza; Mahdi Mahdi; Rika Hariance; Sirajul Fuad Zis; Yulistriani Yulistriani (BULETIN ILMIAH NAGARI MEMBANGUN, 2024)
West Sumatra, one of the provinces in Indonesia, is renowned for its rich cultural heritage and beautiful natural landscapes. Additionally, its agricultural sector significantly contributes to the region's Gross Regional Domestic Product (GRDP), including in Solok Selatan Regency, which boasts the Seribu Rumah Gadang area as its tourism icon. Solok Selatan Regency is also home to Lake Bontak, the only lake in the region, located within the conservation area of Kerinci Seblat National Park (TNKS), one of the gateways for climbing Mount Kerinci. The Independent Conservation Group (KKM) Bangun Rejo has been managing agro-ecotourism by establishing a Tourism Awareness Group (Pokdarwis) and farmer groups. These groups engage in integrated farming, agriculture, and livestock businesses with nature tourism at Lake Bontak. The empowerment of these community groups aims to develop sustainable agro-ecotourism in Solok Selatan Regency. One method used is Focus Group Discussions (FGD) to identify the potential for agro-ecotourism development at Lake Bontak. The outcomes of these activities include the agro-edutourism development concept, the creation of social media accounts for promotion, and the cleaning and installation of tracking paths and tourist activity guides in the Lake Bontak area. Additionally, there is an emphasis on educating the community about conducting tourism activities that prioritize biodiversity conservation within the conservation area to support ongoing environmental knowledge around Lake Bontak. It is hoped that this area will attract both local and international tourists, particularly students and researchers interested in exploring the flora and fauna potential through the agro-edutourism concept.